Penerapan Teknologi Pakan Flushing pada Pembiakan Sapi di Desa Pangkal Jaya, Kecamatan Nanggung, Kabupaten Bogor - Muhammad Baihaqi; Edit Lesa Aditia; Iwan Prihantoro (Agrokreatif: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2023)
The Daarusa'adah farmer group had a cattle breeding program using 20 local heifers. The limited knowledge and skills in managing the farm made the breeding program did not run optimally. The community service program, therefore, aimed to conduct training of cattle production and flushing feed technology application to support breeding program at farmer. This activity was carried out in Pangkal Jaya Village, Nanggung District, Bogor Regency, West Java, through three stages: 1). Training on beef cattle production and breeding program, 2). Assessment of the reproductive organs and health status and 3). Application of flushing feed in beef cattle at farmer level. There were 15 farmers who participated in this program. The data of training questionnaire were analyzed using the Wilcoxon signed-rank test to determine statistic significant differences of their knowledge between before and after the training program. The cattle performance data due to flushing feed application were analyzed descriptively. The results of showed that farmers were increase their knowledge and skills significantly in all production aspects of production and breeding cattle (P<0.05) due to the training program. Application of flushing feed increase the body condition score (BCS) and body weight of the heifers. However, 50% of heifers have ovarian hypofunction based on rectal palpation. Therefore, it can be concluded that the training program of community service activities have succeeded increase the knowledge and skill of farmers. Furthermore, application of flushing feed increases the performance of heifers to support the cattle breeding program.